Ribavirin and Interferon Therapy for Critically Ill Patients With Middle East Respiratory Syndrome: A Multicenter Observational Study. (25th June 2019) - Arabi, Yaseen M; Shalhoub, Sarah; Mandourah, Yasser; Al-Hameed, Fahad; Al-Omari, Awad; Al Qasim, Eman; Jose, Jesna; Alraddadi, Basem; Almotairi, Abdullah; Al Khatib, Kasim; Abdulmomen, Ahmed; Qushmaq, Ismael; et al.
Abstract: Background: The objective of this study was to evaluate the effect of ribavirin and recombinant interferon (RBV/rIFN) therapy on the outcomes of critically ill patients with Middle East respiratory syndrome (MERS), accounting for time-varying confounders. Methods: This is a retrospective cohort study of critically ill patients with laboratory-confirmed MERS from 14 hospitals in Saudi Arabia diagnosed between September 2012 and January 2018. We evaluated the association of RBV/rIFN with 90-day mortality and MERS coronavirus (MERS-CoV) RNA clearance using marginal structural modeling to account for baseline and time-varying confounders. Results: Of 349 MERS patients, 144 (41.3%) patients received RBV/rIFN (RBV and/or rIFN-α2a, rIFN-α2b, or rIFN-β1a; none received rIFN-β1b). RBV/rIFN was initiated at a median of 2 days (Q1, Q3: 1, 3 days) from intensive care unit admission. Crude 90-day mortality was higher in patients with RBV/rIFN compared to no RBV/rIFN (106/144 [73.6%] vs 126/205 [61.5%]; P = .02]. After adjusting for baseline and time-varying confounders using a marginal structural model, RBV/rIFN was not associated with changes in 90-day mortality (adjusted odds ratio, 1.03 [95% confidence interval CI, .73–1.44]; P = .87) or with more rapid MERS-CoV RNA clearance (adjusted hazard ratio, 0.65 [95% CI, .30–1.44]; P = .29). Conclusions: In this observational study, RBV/rIFN (RBV and/or rIFN-α2a, rIFN-α2b, or rIFN-β1a) therapy was commonly used in critically ill MERS patients but was not associated with reduction in 90-day mortality or in faster MERS-CoV RNA clearance. Abstract : In this observational study accounting for baseline and time-varying confounders, ribavirin and recombinant interferon (rIFN-α2a, rIFN-α2b, or rIFN-β1a) therapy was not associated with reduction in 90-day mortality or in faster MERS-CoV RNA clearance.